Agrobacterium-Mediated Transformation of Javanica Rice Plants With A Cry1b Gene Under The Control of Wound-Inducible Gene Promoter - Estiati, Amy; Rachmawati, Syamsidah; Astuti, Dwi; Loedin, Inez Hortenza Slamet (Annales Bogorienses, 2007)
A cry1B synthetic gene of Bacillus thuringiensis has been used for the transformation of the javanica rice plants cv. Rojolele to confer resistance to an important pest yellow stem borer (Scirpophaga incertulas). Embryogenic callus were co-cultivated with the EHA105 strain of Agrobacterium tumefaciens harbouring binary vector pCAMBIA I301 containing cry1B gene under the control of wound inducible gene promoter (mpi), hygromycin resistance gene (hpt) as a selectable marker and intron-containing b-glucuronidase (gus intron) gene as a reporter gene driven by CaMV35S promoter. Previously. our histochemical assay and PCR analysis had proved the integration of cry1B gene into the genome of rice plants at first generation. However, the existence of the gene should remain stable throughout generation. In this study, the presence of the cry1B transgene in rice transgenic plants at second generation was confirmed by Polymerase Chain Reaction (PCR). Insertion of the cry1B gene in the genome of PCR positive plants was verified by Southern blot analysis and showed that integration of cry1B into the genomic DNA of javanica rice plants cv. Rojolele. An effective resistance of transgenic plants against stem borer was verified in bioassays.